Taunton's complete illustrated guide to working with wood - Rae, Andy.; Taunton Press (Newtown, CT : Taunton Press, 2005)
Understanding wood -- Indentifying wood -- Cutting your own wood -- Drying lumber -- Buying lumber -- Storing lumber -- Dealing with wood movement -- Choosing joints -- Selecting your material -- Dimensioning wood -- Working with difficult wood -- Bending wood -- Smoothing and preparing wood -- Gluing and clamping wood -- Finishing wood
The properties of wood -- Identifying wood -- Cutting your own wood -- Drying lumber -- Buying lumber -- Storing lumber -- Dealing with wood movement -- Choosing joints -- Selecting your material -- Dimensioning wood -- Working difficult wood -- Bending wood -- Smoothing and preparing wood -- Gluing and clamping wood -- Finishing wood.
Keywords: Wood; Woodwork